miR-518b Enhances Human Trophoblast Cell Proliferation Through Targeting Rap1b and Activating Ras-MAPK Signal - Liu, Ming; Wang, Yongqing; Lu, Huifen; Wang, Hao; Shi, Xiaoming; Shao, Xuan; Li, Yu-xia; Zhao, Yangyu; Wang, Yan-Ling (Frontiers in Endocrinology, 2018)
Preeclampsia is a pregnancy specific complication defined as newly onset gestational hypertension and proteinuria. Deficiency in placental development is considered as the predominant cause of preeclampsia. Our previous study found that the expression of miR-518b increased significantly in the preeclamptic placentas, indicating the potential participation of this small RNA in the occurrence of preeclampsia. In this study, data analysis using multiple databases predicted Rap1b as a candidate target of miR-518b. An evident decrease in Rap1b expression was observed in preeclamptic placentas when compared with the control placentas, which was negatively correlated with the level of miR-518b. Based on the data of in situ hybridization and immunohistochemistry showing that Rap1b exhibited similar localization with miR-518b in villous cytotrophoblast cells and column trophoblasts, we further explored their function in regulating trophoblast cell proliferation. In HTR8/SVneo cells, exogenous transfection of miR-518b reduced the expression of Rap1b, and dual-luciferase reporter assay validated Rap1b as the direct target of miR-518b. The small RNA could increase the BrdU incorporation and the ratio of cells at S phase, and enhance the phosphorylation of Raf-1 and ERK1/2. Such growth-promoting effect could be efficiently reversed by Rap1b overexpression. The data indicate that miR-518b can promote trophoblast cell proliferation via Rap1b-Ras-MAPK pathway, and the aberrant upregulation of miR-518b in preeclamptic placenta may contribute to the excessive trophoblast proliferation. The study provides new evidence to further understand the etiology of preeclampsia.